Dental eruption: molecular bases. A literature review - De la Cruz Sedano, Gabriela Silvia (2020)
Dental eruption is a dynamic process, which begins when the dentary germ forms in the developmental crypt and finally appears in the mouth. The dental follicle has an important role in the coronal and root formation of the tooth and is essential for tooth eruption, without which the tooth could not erupt. Tooth eruption requires resorption of the alveolar bone that covers the crown of the tooth to form a path to the eruption and biological processes by which the tooth can move through this eruption path. Tooth eruption needs localized and genetically programmed molecular and cellular processes that allow osteogenesis and osteoclastogenesis of the alveolar bone to form the eruption path. The objective of this review was to describe the possible cellular and molecular events that influence the tooth eruption process, since the exact mechanism remains unknown.